Assessment of quality of life in patients with myasthenia - Kalbus, Oleksandr (ScienceRise: Medical Science, 2018)
Aim: to study the quality of life in adult patients with myasthenia, depending on the immunological subtype and the clinical form of the disease. Methods: 96 patients (56 women and 40 men) with myasthenia (71 with generalized, 25 with an ophthalmologic form, respectively) underwent in-depth clinical and neurological, immunological examination tests on MGQoL-15 scale. Results: When evaluated on the MGQoL-15 scale, the average quality of life was 10.34 ± 9.4 points (in ranging from 0 to 31). In patients with ophthalmic myasthenia (class I by MGFA), the quality of life is significantly higher in comparison with patients with generalized form (p<0.05). In the generalized form, quality of life indicators are significantly reduced with increasing severity of the disease (from class II to class IV by classification of MGFA, p<0.05). The level of quality of life does not depend on the detection of antibodies to acetylcholine receptors, antibodies to muscle-specific tyrosine kinase or their absence (p>0.05). Conclusions: The quality of life of patients with myasthenia depends on the severity of the disease and does not depend on the immunological subtype of the disease. The highest indicators of quality of life are observed in patients with ocular form of myasthenia, which is explained by the lesser influence of neurological manifestations of the disease on everyday life, habits, work of patients. Reducing the severity of manifestations of myasthenia leads to an improvement in the quality of life of patients